Exploring Rogers-Ramanujan-Type Identities Modulo 9, 11, 18, and 22 - Vijayan, Deepthi (Journal of Research in Vocational Education, 2025)
In this paper, some identities of Rogers_Ramanujan Type related to modulo 9, 11, 18 and 22 is derived with the incorporation of generalized Bailey pairs and some standard results established by Andrew V. Sills [1] using some q − difference relations.